Controle coerente da excitação de modos topológicos em condensados de Bose-Einstein - Silva, Leonardo Brito da (2019)
In this project were carried out a study on dynamics control of one dimensional Bose- Einstein condensates of dilute gases by development and application of techniques on systems that are described by Gross-Pitaevskii equation. Were built numeric codes able to return states and energies of condensate nonlinear hamiltonian and also simulate the dynamics of this one when driven by external fields. Therefore, it was possible the observation of condensate behavior under several shapes of space- temporal modulating fields, that are divided in two classes, the first one, the trap modulating, and the second one, the scattering length modulating. The objective of this analysis is to investigate the different natures modulations combined to induce target transitions, in order to built condensates in topological modes by amplitude of the two pathways interference. We noticed that the double modulation can drive the desired transition in a shorter time than only one modulation without significant loss of atoms during fields action and it presents a interesting response to fields relative phase , frequency modulation and fields dalay, in such a way that target transition can be submitted to different ways of Coherent Control. It can reduce the time of transition interfering fields and can control the fraction migrated, such as to interrupt the process without the need to turn off the fields.